In silico Analysis of Acyl-CoA-Binding Protein Expression in Soybean - Azlan, Nur Syifaq; Guo, Ze-Hua; Yung, Wai-Shing; Wang, Zhili; Lam, Hon-Ming; Lung, Shiu-Cheung; Chye, Mee-Len (Frontiers in Plant Science, 2021)
Plant acyl-CoA-binding proteins (ACBPs) form a highly conserved protein family that binds to acyl-CoA esters as well as other lipid and protein interactors to function in developmental and stress responses. This protein family had been extensively studied in non-leguminous species such as Arabidopsis thaliana (thale cress), Oryza sativa (rice), and Brassica napus (oilseed rape). However, the characterization of soybean (Glycine max) ACBPs, designated GmACBPs, has remained unreported although this legume is a globally important crop cultivated for its high oil and protein content, and plays a significant role in the food and chemical industries. In this study, 11 members of the GmACBP family from four classes, comprising Class I (small), Class II (ankyrin repeats), Class III (large), and Class IV (kelch motif), were identified. For each class, more than one copy occurred and their domain architecture including the acyl-CoA-binding domain was compared with Arabidopsis and rice. The expression profile, tertiary structure and subcellular localization of each GmACBP were predicted, and the similarities and differences between GmACBPs and other plant ACBPs were deduced. A potential role for some Class III GmACBPs in nodulation, not previously encountered in non-leguminous ACBPs, has emerged. Interestingly, the sole member of Class III ACBP in each of non-leguminous Arabidopsis and rice had been previously identified in plant-pathogen interactions. As plant ACBPs are known to play important roles in development and responses to abiotic and biotic stresses, the in silico expression profiles on GmACBPs, gathered from data mining of RNA-sequencing and microarray analyses, will lay the foundation for future studies in their applications in biotechnology.